Produktivitas sapi peranakan ongole pada pola pemeliharaan sistem perkampungan ternak dan kandang individu di kabupaten Bantul = Productivity of Ongole Grade Cattle in Group and Individually System in Bantul Regency - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The research was proposed to study ongole cross breed cattle productivity that raised on group system in Bantul Regency, Yogyakarta. The research was conducted in July until October 2002 used 55 farmers with gruop system as our respondent. As comparison, used 58 farmers with individual system. Each rearing system used 61 ongole grade cows and their offspring. Observed variables were average daily gain, feed consumption, feed conversion, feed cost per gain, weaning age, post partum estrus, post partum mating, service per conception, calving interval, raising management and problems that arose in group system. The result of survey method, interview and direct weighing showed that average daily gain, feed cost per grain, post partum estrus, post partum mating, service period, S/C and calving interval showed insignificant difference (P>0,05). Similarly, total score for raising management on individual and group system showed insignificant difference (P>0,05). On the other hand, 13-24 months old steer's average daily gain and feed conversion on group system were better and significantly difference (P